DEVELOPMENT OF COLLABORATIVE LEARNING MODELS TO IMPROVE STUDENT'S WRITING SKILLS CLASS V SD NEGERI 065011 SUB-DISTRICT MEDAN CITY - Norita Butarbutar; Sutikno Sutikno; Rahmat Kartolo (International Journal of Ethno-Sciences and Education Research, 2022)
The low interest and talent of fifth grade students at SD Negeri 065011, Medan Selayang Subdistrict, Medan City, for the 2021-2022 academic year in writing activities is caused by the absence of creativity made by educators in teaching students. For this reason, it is necessary to develop an innovative learning model that can make students more active in the process of learning to write. The learning model to be developed in this research is a collaborative learning model. The collaborative learning model is one of the "Student-Centered Learning" (SCL) models. The purpose of this study was to describe the effectiveness of the use of collaborative learning models in improving the writing skills of fifth graders at SD Negeri 065011, Medan Selayang Subdistrict, Medan City in the 2021-2022 academic year. The research method used in this research is the research & development method. The research subject of this development product is the validator. The object of research in this study is a writing learning model, namely a collaborative learning model that is implemented in fifth grade students of SD Negeri 065011, Medan Selayang District, Medan City in the 2021-2022 academic year. The instrument used to obtain research data using non-test instruments and test instruments. The results of this study indicate that the collaborative learning model is effective in improving the skills of writing descriptive text by fifth grade students of SD Negeri 065011, Medan Selayang District, Medan City in the 2021-2022 academic year, where before the process of developing the collaborative learning model was in the sufficient category and then increased to good after the process of developing cooperative learning models in class V of SD Negeri 065011, Medan Selayang District, Medan City, for the academic year 2021-2022.